A Biosimilarity Study Between QX001S and Ustekinumab in Healthy Chinese Male Subjects - Gao, Lei; Li, Qingmei; Zhang, Hong; Wu, Min; Fang, Min; Yang, Lizhi; Li, Xiaojiao; Liu, Jingrui; Li, Cuiyun; Chen, Hong; Zhu, Xiaoxue; Ding, Yanhua; et al. (Frontiers in Pharmacology, 2021)
Objective: To evaluate the tolerance, variability, and pharmacokinetics (PK) of QX001S, a biosimilar for Ustekinumab, in healthy Chinese men. Methods: One hundred and seventy-eight healthy men were recruited in this randomized, double-blind, single-dose, two-arm, parallel study, and received 45 mg of QX001S or Ustekinumab in a single subcutaneous injection. PK, immunogenicity, and tolerance were evaluated in all participants for a period of 113 days. Results: The similarity between the two drugs was determined by comparing the baseline characteristics for each drug. The PK parameters were similar in the two groups: QX001S (n = 89) and Ustekinumab (n = 88). The 90% confidence intervals (CIs) for the geometric mean ratio (GMR) of QX001S to the reference (Ustekinumab) for the maximum observable serum concentration (Cmax), area under the curve (AUC) from zero to the final quantifiable concentration (AUC0–t), and AUC from zero to infinity (AUC0–∞) were 100.90-118.68%, 98.71-115.26%, and 98.49-115.81%, respectively, which were within the predefined bioequivalence limit of 80.00 – 125.00%. High inter-subject variability (ranging from 32.0 to 33.5%) was observed. A total of 17 participants (19.1%) in the QX001S group and 36 (40.9%) in the Ustekinumab group developed anti-drug antibodies (ADA) after administration. Nevertheless, the ADA did not affect the outcomes of the bioequivalence tests. Adverse reactions were recorded in 38 individuals injected with QX001S and 37 injected with Ustekinumab. The most common adverse reactions were upper respiratory infection and elevated alanine aminotransferase. Conclusion: Our study ratified pharmacokinetic biosimilarity between QX001S and Ustekinumab, with high variability between subjects.